Determination of the virulence status of Clostridium perfringens strains using a chicken intestinal ligated loop model is important for understanding the pathogenesis of necrotic - Nicolas Deslauriers; Lila Maduro; Dion Lepp; Joshua Gong; Mohamed Faizal Abdul-Careem; Martine Boulianne (Poultry Science, 2024)
ABSTRACT: Necrotic enteritis (NE) is a poultry intestinal disease caused by virulent strains of the bacterium Clostridium perfringens (C. perfringens). This anaerobic bacterium produces a wide range of enzymes and toxins in the gut which leads to NE development. It is generally accepted by the poultry veterinarians that netB-positive C. perfringens strains are virulent and netB-negative strains do not cause NE. However, NE pathogenesis remains unclear as contradictory results have been reported. The use of experimental in vivo models is a valuable tool to understand the pathogenesis of a disease. In this study, a chicken ligated loop model was used to determine the virulence status of 79 C. perfringens strains from various geographical locations, sources, and genotype profiles. According to our model and based on histologic lesion scoring, 9 C. perfringens strains were classified as commensal, 35 as virulent, and 34 as highly virulent. The virulence of only 1 C. perfringens strain could not be classified as its lesion score was variable (from <10 to >15). In general, NE lesions were more severe in intestinal loops inoculated with netB-positive C. perfringens strains than those inoculated with netB-negative strains. The prevalence of netB among strains classified as commensal, virulent, and highly virulent was 56% (5/9), 54%, (19/35), and 59% (20/34). These results suggest that NetB is not required to cause NE lesions and that other factors are also involved. The classification of the virulence status of C. perfringens strains should not be based solely on the presence or absence of this toxin. Therefore, the use of an in vivo model is essential to distinguish commensal from virulent strains of C. perfringens.